Impacts of Planting System, Plant Age, and Climatic Variables on Pests And Predators in Common Bean Fields - Barros, Emerson Cristi de; Dângelo, Rômulo Augusto Cotta; Sacramento, Jose Augusto Amorim Silva do; Taube, Paulo Sergio; Souza, Sorrel Godinho Barbosa de (Journal of Agricultural Studies, 2022)
Understanding the environmental influences on insect pests and predator dynamics is essential for the development of integrated pest management strategies for common bean plants. This study aimed to determine the effects of the planting system, plant age, climatic variables, and predator populations on common bean pests under field conditions. Planting systems, plant age, climatic variables, and the abundance of insect pests and predators were evaluated under field conditions over two years in three planting seasons per year. A generalized linear mixed model (GLMM) was adjusted to quasi-Poisson and negative binomial distributions. Model selection was based on the Akaike information criterion. According to the selected model, chewing, sap-sucking, cell content-sucking, and boring insects were influenced by plant age, planting system, air temperature, rainfall, and relative humidity. Additionally, predators including spiders, beetles, ants, pirate bugs, and ladybugs were influenced by plant age, air temperature, rainfall, relative humidity, and abundance of insect pests on common bean plants. This information is essential for conservation biology programs and integrated pest management.